The Governance Role of Independent Directors in Indonesian Family and Non-Family Firms - Atmaja, Lukas Setia; Hidayat, Athalia Ariati (Jurnal Keuangan dan Perbankan, 2021)
This paper examines the governance role of independent directors in Indonesia using family and non-family firm samples. The literature suggests that independent directors can mitigate conflicts of interest between controlling families and non-controlling or minority shareholders among family firms. This study utilizes panel data of firms listed from 2005 to 2019, comprising 4.865 firm-year observations. Our result reveals that the performance of family firms is significantly worse than that of non-family firms measured by Tobin’s Q and that among family firms, independent directors or commissioners have an insignificance impact on firm value. Our findings support the expropriation theory and are not in line with the notion that independent directors can mitigate agency problems among family firms. Our analysis, however, provides strong evidence that independent directors or commissioners in non-family firms positively affect firm performance.JEL: D74, G32, H11